Intraoperative infrarenal aortic balloon occlusion in pregnancies with placenta accreta spectrum disorder - Mengdie Luo; Junxing Li; Xiaofeng Yang; Qiang Huang; Mengwei Huang; Jie Mei (IMR Press, 2021)
Background: The objective of this study was to evaluate the efficacy of intraoperative aortic balloon occlusion (IABO) during caesarean section for placenta accreta, increta or percreta and explore the relationship between different profile balloon catheters and catheter-related complications. Methods: This retrospective case control study included 295 patients with pathologically confirmed placenta accreta spectrum (PAS) disorder at the Sichuan Academy of Medical Sciences & Sichuan Provincial People's Hospital between 2013 and 2019. The characteristics of 162 patients who had aortic balloon occlusion (balloon group) were compared with those of 133 patients who had no catheterization (control group). Results: There were significant differences between the two groups in estimated blood loss, calculated blood loss, number of transfusions, transfused packed red blood cells (PRBCs), haemoglobin reduction, operation time and caesarean hysterectomy (P < 0.05). Regarding different PAS disorders, the estimated blood loss among women with placenta accreta and placenta increta was lower in the balloon group (n = 32 and 102, respectively) than in the non-balloon group (n = 33 and 85; P = 0.04 and P < 0.01, respectively). Only the placenta increta group showed a significant difference (P < 0.01) in transfused PRBCs. In patients who used the low-profile balloon catheters, we found a significant reduction in catheter-related complications compared with the high-profile group (n = 52 vs. 110, P = 0.04). Conclusions: Our study demonstrated that intraoperative infrarenal aortic balloon occlusion was effective in both reducing intraoperative haemorrhage and blood transfusion, and in preventing hysterectomy during caesarean section for pathologically diagnosed placenta accreta and increta. Low-profile balloon catheters can reduce catheter-related complications.